2008
DOI: 10.1002/cne.21763
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural examination of diffuse and specific tectopulvinar projections in the tree shrew

Abstract: Two pathways from the superior colliculus (SC) to the tree shrew pulvinar nucleus have been described, one in which the axons terminate in dense (or specific) patches and one in which the axon arbors are more diffusely organized J. . As predicted by Lyon et al. ([2003] J. Comp. Neurol. 467:593-606), we found that anterograde labeling of the diffuse tectopulvinar pathway terminated in the acetylcholinesterase (AChE)-rich dorsal pulvinar (Pd), whereas the specific pathway terminated in the AChE-poor central pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
116
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(128 citation statements)
references
References 56 publications
10
116
1
Order By: Relevance
“…Indeed, this inhibitory circuit could contribute to the disengagement of attention at an initial location (usually more central/nasal) that precedes a shift of attention to a peripheral field (Posner 1980). In this case, the changes in excitability in the visuosensory layers would be transmitted to attentional circuits in the cortex via the ascending collicular projections through the thalamus (Chomsung et al 2008;Karten et al 1997) to mediate rapid shifts of attention to a new location and disengagement of attention from the current location. Consistent with these ideas, increased excitability of visuosensory neurons in the SC was recently reported in a rat model of attention deficit disorder (Clements et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this inhibitory circuit could contribute to the disengagement of attention at an initial location (usually more central/nasal) that precedes a shift of attention to a peripheral field (Posner 1980). In this case, the changes in excitability in the visuosensory layers would be transmitted to attentional circuits in the cortex via the ascending collicular projections through the thalamus (Chomsung et al 2008;Karten et al 1997) to mediate rapid shifts of attention to a new location and disengagement of attention from the current location. Consistent with these ideas, increased excitability of visuosensory neurons in the SC was recently reported in a rat model of attention deficit disorder (Clements et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Similar examples of driver-like convergence illustrate the complexity of thalamic organization. The dorsal thalamus may be divided not only into "first order" (driven by ascending peripheral input) or "higher order" (driven by descending cortical input) nuclei (Guillery and Sherman, 2002), but also "second order" nuclei driven by convergent, ascending inputs (Kelly et al, 2003;Smith et al, 2007;Chomsung et al, 2008;Masterson et al, 2009Masterson et al, , 2010, or nuclei that contain unique combinations of ascending and descending driver-like inputs (Baldauf et al, 2005;Rovo et al, 2012;Groh et al, 2014). Such diversity may dramatically increase the computational capabilities of the thalamus, reflecting its essential roles in sensory, motor, and sensory-motor circuits.…”
Section: Discussionmentioning
confidence: 99%
“…As schematically illustrated in Figure 11, this homology is based to a large extent on commonalities in the projections of the superficial (visual) layers of the superior colliculus (SC), or optic tectum, to the primate pulvinar nucleus, rodent/carnivore LPN, and avian nucleus rotundus (Harting et al, 1973b;Robson and Hall, 1977;Berson and Graybiel, 1978;Mooney et al, 1984;Takahashi, 1985;Abramson and Chalupa, 1988;Luppino et al, 1988;Hutsler and Chalupa, 1991;Villeneuve and Casanova, 2003;Kelly et al, 2003;Chomsung et al, 2008;Masterson et al, 2009Masterson et al, , 2010Baldwin et al, 2011;Wei et al, 2011b;Fredes et al, 2012;Baldwin et al, 2013). Because of these similarities, we will refer to this region of the mouse thalamus as the pulvinar nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Seven tree shrews were used to investigate the distribution and morphology of the projections to the temporal lobe labeled by injections of BDA in two areas of the pulvinar, the dorsal pulvinar (PD) (3 tree shrews) and the central pulvinar (PC) (4 tree shrews). Several of these animals were also used for previous studies (Chomsung et al 2008. All methods were approved by the University of Louisville Animal Care and Use Committee and conform to the National Institutes of Health guidelines.…”
Section: Chapter 2: Methodsmentioning
confidence: 99%
“…PD carries a representation of the upper half of the field of vision from the superior colliculus while PC carries a representation of the lower vision field (Chomsung et al 2008;Dang et al 2012). This matches data from Lyon et al (2003), where they also found that only PD in the pUlvinar nucleus projected to TP.…”
Section: Secondary Visual Pathway Temporal Cortical Areasmentioning
confidence: 99%